Models of efficiency of functioning in trading enterprises under conditions of economic growth - Ilyash Olha; Vasyltsiv Taras; Lupak Ruslan; Get’manskiy Volodymyr (Bulletin of Geography. Socio-Economic Series, 2021)
The socio-economic situation in Ukraine suggests that there is insufficient research into the applicability of the model of economic development in forecasting the economic environment in which trade enterprises function. Researchers into issues relating to the efficiency of enterprises’ functioning focus their interest on comprehensively describing efficiency indicators and determining the factors influencing it. There continues to be insufficient work on measuring efficiency and the extent to which it is limited by types of economic growth (development), based on the theory of marginal product of George Clark and the results of multiple models of production and trade functions (P. Douglas, R. Solow, E. Denison, Harrod, Samuelson-Hicks, Domar and others). Therefore, this study focuses on the process of assessing the effectiveness of trading enterprises in the trade sector in 2010–18 in conditions of economic growth and an economic downturn. This article aims to examine the models of efficient functioning of trading enterprises in conditions of economic growth. It is evidenced that the criterion for measuring efficiency is the evaluation of static and dynamic efficiency of trade activities, which allows changes in the used assets to be taken into account and testifies to the integration of diminishing returns and economic fluctuations in macro and microsystems. The article shows that in order to qualitatively and completely evaluate the efficiency of the functioning of trading enterprises, it is necessary to consider all possible factors. According to Clark's law, the authors substantiate an approach to evaluating performance based on simple one-factor models; the approach evidences that future studies seeking ways to improve efficiency, but that focus on changes in resources, will be erroneous, unjustified, and will most likely reduce the effectiveness of the resource under study. This model will help: determine and forecast the efficiency of enterprises at any point in the economic cycle; provide the necessary information on the required amount of investment, on depreciation rates, and on the optimal amount of labour potential of an enterprise; and define the volume of expected income during economic crisis or recovery. Some applied recommendations in terms of managing the efficiency of trading enterprises are aimed at solving the methodological problem of constructing isoquant maps for a particular product line group and at selecting the optimal predictor for forecasting trade processes. The practical value of the proposed model also lies in improving the parameters of positioning of the enterprise's goods in target market segments, reducing operating costs, accelerating the turnover of inventories and withdrawing illiquid current assets, and increasing the efficiency of retail areas.